Analisis Rangkaian Mesh dengan Aplikasi Android Proto Circuit dan Pembuktiannya dengan Eksperimen Real - Fuada, Syifaul; Fathul Jannah, Nusaibah; Zarkasyi, Nurfaiz; Fatih Hady, Muhammad (Universitas Darul Ulum, 2024)
The existence of current technological developments can affect education in tertiary institutions because there is a simulator that can make it easier for students to understand electrical circuits, and researchers get a simulator, namely the Proto Circuit Android App. This study aims to reveal the differences in the measurement values in the 3-loop mesh circuit. The 3-loop mesh circuit is a method or method used to analyze an electrical circuit which usually consists of several interconnected loops. At the beginning of the practicum using a simulator called Proto Circuit Android App to make a design or description of a 3-loop mesh electrical circuit in visual form. The ters application is also a very popular and widely used electronic circuit simulation application. However, there is no research that specifically compares the simulation results with the Proto Circuit Android App and physical practice on a 3-loop mesh circuit. Therefore, this study complements this energy by measuring the measurement results of the three methods. The research results show that the results from the simulator and real are quite accurate but there are differences in values caused by imperfections in components, measurement inaccuracies, or other factors that affect circuit performance in real conditions. This research can be used for readers to operate the Proto Circuit Android App simulator and study the 3-loop mesh circuit.